Peran mindfulness sebagai moderator pada hubungan antara komunikasi interpersonal dan kepuasan pernikahan - Wulansari, Indri; Riasnugrahani, Missiliana; Rajagukguk, Robert Olan (Jurnal Psikologi Ulayat, 2024)
This study aims to provide an overview of the role of mindfulness as a moderator in the relationship between interpersonal communication and marital satisfaction among husbands and wives married for over five years. Participants in this study were 188 husbands or wives who met the criteria of being married for over five years and living with their partners in the city of Bogor. Participants were selected using a purposive sampling technique. Each participant completed the Enrich Marital Satisfaction Scale (EMS), Five Facet Mindfulness Questionnaire (FFMQ), and interpersonal communication (IC) Scales. Using Hayes’ PROCESS Model 1 analysis technique, the study found that mindfulness significantly moderates the relationship between interpersonal communication and marital satisfaction, although its effect weakens this relationship.